2021
DOI: 10.3389/fped.2021.713921
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Case of Leukocyte Adhesion Deficiency, Type III Presenting With Impaired Platelet Function, Lymphocytosis and Granulocytosis

Abstract: Fermitin family homolog 3 (FERMT3), alternatively kindlin-3 (KIND3), is an integrin binding protein (of 667 residues) encoded by the FERMT3 gene. The molecule is essential for activating integrin αIIbβ3 (the fibrinogen receptor) on platelets and for the integrin-mediated hematopoietic cell (including platelets, T lymphocytes, B lymphocytes, and granulocytes) adhesion. Its defects are associated with impaired primary hemostasis, described as “Glanzmann's thrombasthenia (MIM#273800)-like bleeding problem.” The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…A key feature of the current case is lymphocytosis (75%), with occasionally activated forms. This is consistent with previous findings from a LAD-III case presented by Yahya et al who reported persistent lymphocytosis and agranulocytosis [4]. Leukocytosis was quite prominent in the present case (26.5x10 9 /L).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A key feature of the current case is lymphocytosis (75%), with occasionally activated forms. This is consistent with previous findings from a LAD-III case presented by Yahya et al who reported persistent lymphocytosis and agranulocytosis [4]. Leukocytosis was quite prominent in the present case (26.5x10 9 /L).…”
Section: Discussionsupporting
confidence: 94%
“…FERMT3 genes encode for kindlin-3, a protein involved in the activation of integrin which ensures the adhesion of platelets, granulocytes, and lymphocytes. In LAD-III, there is a variation of the FERMT3 gene that impairs integrin function [ 4 ]. LAD-III manifests as abnormal integrin activation during the second phase of the adhesion cascade [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kindlin-3-deficient leukocytes fail to arrest and extravasate into inflammatory tissues which causes leukocyte adhesion deficiency syndrome type III; this manifests in massive bleeding and recurrent infection [46]. Patients with kindlin-3 gene variants present with impaired platelet function, lymphocytosis and granulocytosis [47].…”
Section: Interaction Of the β3 Nxxy 759 Motif With Kindlinmentioning
confidence: 99%